Developing students reading competence through cognitive strategy (Journal of Science-Innovative Research in Uzbekistan, 2025)
In modern education, developing reading competence is critical for language learning. This article examines how cognitive strategies—such as prediction, summarizing, questioning, and clarifying—enhance students’ reading comprehension and analytical skills. It emphasizes metacognitive awareness and active reading techniques to foster deeper text engagement. A review of pedagogical approaches and classroom practices underscores the importance of strategic instruction in cultivating autonomous, confident readers. Findings indicate that systematic integration of cognitive strategies in reading lessons improves academic performance and promotes long-term language proficiency.